INFECTIOUS DISEASES IN CHILDREN AGED 4-5 YEARS: A REVIEW OF COMMON CONDITIONS, PREVENTION, AND MANAGEMENT - Аслиддин Холматович Жалилов (Ta'lim innovatsiyasi va integratsiyasi, 2024)
Abstract:  Children  aged  4  to  5  years  are  at  an  increased  risk  for  various infectious  diseases  due  to  their  developing  immune  systems,  frequent  social interactions,  and  exposure  to  different  environments.  This  age  group  is  highly susceptible  to  respiratory  infections,  gastrointestinal  illnesses,  and  childhood  viral diseases. The article reviews common infectious diseases in children aged 4-5 years, including their clinical presentations, preventive measures, and management strategies. Emphasis is placed on vaccination, hygiene practices, and early intervention to mitigate the impact of these diseases.